Juegos autóctonos y populares del pueblo montubio como elementos para fortalecer el turismo en el Cantón Vinces - Morán Arévalo, Joel Israel (2020)
This case study aims to identify the indigenous and popular games of the Montubio people in order to strengthen the cultural roots of Canton Vinces, because they constitute the cultural heritage of the place and witness the way in which a society or culture relates to its environment when performing its practice. Today, cultural heritage is linked to the most pressing challenges facing humanity, contributing to the revaluation of culture and identity. The scarce knowledge of tourist activities such as native games, is one of the main impediments to a good use and development of tourism in Vinces canton. The practice of mountain games is important to strengthen the cultural identity of the mountain peoples of Canton Vinces and the tourist development of the place. The promotion of the montubian culture plays a fundamental role, which will allow to know the different native and popular games, the sector where it is carried out, and the development of tourist activities that allow to attract the cultural tourism to the city. It is important to emphasize the economic sustainability that cultural heritage provides for the tourism sector by finding a balance between taking advantage of it and preserving its richness for future generations.